Which Is Better for Liver SBRT: Dosimetric Comparison Between DCAT and VMAT for Liver Tumors - Moon, Young Min; Jeon, Wan; Yu, Tosol; Bae, Sang Il; Kim, Jin Young; Kang, Jin-Kyu; Choi, Chul Won (Frontiers in Oncology, 2020)
Stereotactic body radiotherapy (SBRT) is currently well adopted as a curative treatment for primary and metastatic liver tumors. Among SBRT methods, dynamic conformal arc therapy (DCAT) and volumetric-modulated arc therapy (VMAT) are the most preferred methods. In this study, we report a comparison study measuring the dose distribution and delivery efficiency differences between DCAT and VMAT for liver SBRT. All patients who were treated with SBRT for primary or metastatic liver tumors with a curative aim between January 2016 and December 2017 at DIRAMS were enrolled in the study. For all patients, SBRT plans were designed using the MC algorithm in Monaco TPS (version 5.1). The planning goals were set according to the RTOG 0813, RTOG 0915, and RTOG 1112 protocols. A plan comparison was made on the metrics of dose volume histogram, planning and delivery efficiency, monitor unit (MU), and dosimetric indices. PTV coverage was evaluated using the following: Dmean, D95%, D98%, D2%, D50%, Dmax, V95%, heterogeneity index (HI), and conformality index (CI). For DCAT and VMAT, respectively, the Dmean was 5942.8±409.3 cGy and 5890.6±438.8 cGy, D50% was 5968.8±413.1 cGy and 5954.3±405.2 cGy, and CI was 1.05±0.05 and 1.03±0.04. The D98% and V95% were 5580.0±465.3 cGy and 20.4±12.0 mL for DCAT, and 5596.0±478.7 cGy and 20.5±12.0 mL for VMAT, respectively. For normal liver, V40, V30, V20, V17, V5, Dmean, Dmax were evaluated for comparison. The V30, V20, and V10 were significantly higher in DCAT; other parameters of normal livers showed no statistically significant differences. For evaluation of intermediate dose spillage, D2cm(%) and R50% of DCAT and VMAT were 45.8 ± 7.9 and 5.6 ± 0.9 and 45.1 ± 6.7 and 5.5 ± 1.2, respectively. Planning and delivery efficiency were evaluated using MU, Calculation time, and Delivery time. DCAT had shorter Calculation time and Delivery time with smaller MU. MU was smaller in DCAT and the average difference was 300.1 MU. For liver SBRT, DCAT is an effective alternative to VMAT plans that could meet the planning goals proposed by the RTOG SBRT protocol and increases plan and delivery effectiveness, while also ignoring the interplay effect.